2009
DOI: 10.1002/dmrr.977
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of 1‐α‐hydroxyvitamin D3 on residual β‐cell function in patients with adult‐onset latent autoimmune diabetes (LADA)

Abstract: Our data suggest that 1-alpha(OH)D3 plus insulin therapy can preserve pancreatic beta-cell function in patients with LADA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 28 publications
1
69
1
2
Order By: Relevance
“…In addition, the onset that occurs at a young age also affects the levels of C-peptide [39]. This result is different from the studies conducted in China where there was a significant positive correlation between vitamin D levels and Cpeptide levels [33]. Similarly, the results of a study conducted in Boston showed a significant positive correlation between vitamin D and C-peptide levels [27].…”
Section: Subject Characteristicscontrasting
confidence: 59%
See 1 more Smart Citation
“…In addition, the onset that occurs at a young age also affects the levels of C-peptide [39]. This result is different from the studies conducted in China where there was a significant positive correlation between vitamin D levels and Cpeptide levels [33]. Similarly, the results of a study conducted in Boston showed a significant positive correlation between vitamin D and C-peptide levels [27].…”
Section: Subject Characteristicscontrasting
confidence: 59%
“…Seventy percent of patients treated with 1-alpha(OH)D 3 of their FCP concentrations persisted or increased after 1 year of treatment, while only 22% of the patients treated with insulin alone had stable FCP levels. Further analysis with different time periods of diabetes showed that better beta-cell beta functions were maintained (reflected significantly higher FCP and PCP levels) in the group receiving 1-alpha(OH)D 3 therapy plus Insulin [33]. Research in Iran, where the intervention group received alfacalcidol 0.25 µg twice daily, while the control group received placebo.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…The outcome of that study shows that such a trial is feasible. A Chinese intervention trial in patients with late-onset autoimmune diabetes reported that the daily use of 0.5 lg alphacalcidol (1a-hydroxyvitamin D) for 12 mo resulted in better preserved b cell function (28).…”
Section: Vitamin D and Vitamin Ementioning
confidence: 99%
“…Debe mencionarse que un estudio aislado muestra que la adición de vitamina D (1 α hidroxi D3) podría colaborar a preservar la reserva pan creática en pacientes con LADA, en asociación a la insulinoterapia 30 .…”
Section: Insulinaunclassified